Diagnosis of Chlamydia psittaci pneumonia using targeted next-generation sequencing: case report and clinical characteristics statistics - Yu, Miao; Wang, Wenbin; Zhou, Huajuan; Kumar, Amit; Zhao, Xiaoli; Qian, Fengfei; Zhong, Xiaohua; Nie, Chuanhua; Sukanya, Roy (Frontiers in Medicine, 2025)
Chlamydia psittaci (Cps) is a Gram-negative intracellular bacterium with birds as its main host. Humans are mainly infected through contact with birds and poultry. The main route is through inhalation of aerosols contaminated by animal excrement through the respiratory tract. The main manifestation after infection is pneumonia, and in severe cases, it can lead to multiple organ failure. Targeted Next-generation Sequencing (tNGS) can detect rare pathogens that are difficult to detect with traditional detection methods, which has continuously improved the detection rate of Cps. This article reports 12 cases of psittacosis pneumonia diagnosed by tNGS of bronchoalveolar lavage fluid (BALF) obtained by bronchoscopy or sputum. The cases are improved after regular treatment, and the clinical characteristics are analyzed at the same time.